Activation/deactivation behavior of nano-NiOx based anodes towards the OER: Influence of temperature. (20th June 2018) - Sayed, Doha M.; El-Nagar, Gumaa A.; Sayed, Sayed Y.; El-Anadouli, Bahgat E.; El-Deab, Mohamed S.
Abstract: Ni-based catalysts have shown promise activity towards the oxygen evolution reaction (OER). The stability and the activity of the Ni-based catalysts are crucial parameters that gained a lot of interest recently. This paper addresses the effect of the preparation temperature ( T p ) on the electrocatalytic activity of nickel oxide nanostructures modified glassy carbon (nano-NiOx/GC) electrode towards the OER. Increasing T p, beyond room temperature ( r.t. ), results in enhancing the kinetics of the OER demonstrated in the values of the exchange current density ( i o ) and the onset potentials of the OER. The effect of T p is reflected on the morphology and size of NiOx, that is increasing T p results in decreasing their particle size. Elevated T p enhances the OER as a result of increasing the population of the electroactive NiOx phases as indicated from their respective XRD patterns. Rapid degradation of the catalytic activity of nano-NiOx/GC electrode towards the OER is observed upon prolonged electrolysis at r.t. Cycling the potential several times between 0.85 and 1.65 V vs. RHE restores the activity to various extents depending on the measurement temperature ( T m ). Graphical abstract: Impact of passivation temperature on the relative enrichment of NiOx phases and the corresponding OER activity in alkaline medium.Image 1 Highlights: Ni-based catalysts (nano-NiOx) are promising towards the OER. The passivation temperature ( T p ) affects the activity and stability of nano-NiOx. Increasing T p, reduces the particle size of nano-NiOx. Elevated T p increases the population of the electroactive NiOx phases. The stability of nano-NiOx is probed at elevated temperatures.